(untitled) (Jurnal Sustainable, 2021)
Islamic religious education at SMAS Taruna Tunas Bangsa Baturaja-South Sumatra is the topic of this study because of its importance in shaping the students’ religious identities and personalities. This research explores the process of Islamic religious education in creating religious identity and personality for pupils. This study is classified as qualitative because of its focus on providing descriptive details about the topic at hand. Interviews, observations, and written records are all used in data collection. Methods for analyzing data at every step of the research process include data collection, presentation, and verification. Triangulation is used to verify the reliability of the study’s data, and it provides triangulation across time, methodologies, and sources. The findings and discussion suggest that the process of Islamic religious education at SMAS Taruna Tunas Bangsa has been successful in helping students form their religious identity and personality. Indicators of the effectiveness of building a healthy religious identity and character in pupils via Islamic religious education include the involvement of the principal, instructors, and excellent engagement of students. Religious instruction in Islam has played a significant role in shaping morally upright citizens. The school works toward this goal via various means, including education in moral and ethical principles, promoting social consciousness, encouraging regular religious practice, and developing an appreciation for and knowledge of students’ diverse religious backgrounds. Students’ feeling of belonging to the Muslim community is bolstered when they learn about their religion’s rich history, culture, and rituals in the classroom.